Exploring ethnomathematics in donggala woven based on geometry and calculus concepts - Indah Suciati; Hajerina Hajerina; Dewi Sri Wahyuni; Wahyuni H. Mailili; Nurhalida Sartika (Fakultas Tarbiyah Universitas Ibrahimy, 2024)
Donggala woven has various patterns that can be used in the mathematics learning process. Qualitative research using the ethnographic method explored ethnomathematics in Donggala weaving based on geometry and calculus concepts. The data collection techniques were literature review, observation, interviews, and documentation. Observations were made at the Job Training Institution (JTI) and shops selling Donggala fabrics, and interviews were conducted with the head of the Donggala Weaving Association in the city of Palu. Data were analyzed using the Miles & Huberman model and triangulated based on sources, methods, and time. The findings show that Donggala weavings can be explored in the mathematics learning process to find geometry concepts (lines and angles and two-dimensional shapes), geometry transformations, and function graphs in calculus. The use of Donggala woven fabric is also intended to make learning more meaningful because it can be a concrete example of the mathematical concept and, at the same time, introduce local wisdom through mathematics learning.